Topical Fibronectin Improves Wound Healing in Postmastectomy Breast Cancer Radiation Therapy : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Breast cancer is the most common cancer among women worldwide. Breast cancer provides an excellent example of how multidisciplinary management has improved patient outcomes. This paper synthesizes the complex and evolving evidence regarding the role of radiation therapy after mastectomy. Although substantial evidence indicates that radiation therapy can reduce the risk of locoregional failure after mastectomy. This therapy is known as PMRT. Postmastectomy radiotherapy (PMRT) is an essential component of combined therapy for early‐stage, high‐risk breast cancer. Breast reconstruction (BR) is often considered for patients with breast cancer who have undergone mastectomy. There has been a considerable amount of discussion about the optimal approach to combining PMRT with BR in the treatment of breast cancer. PMRT may increase the risk of complications and prevent good aesthetic results after BR, while BR may increase the complexity of PMRT and the radiation dose to surrounding normal tissues. The goal of a PMRT plan is to achieve optimal coverage of the target volume while minimizing the irradiation dose to normal tissues. The purpose of this review is to give a broad overview and summary of the current topical fibronectin improves wound healing in postmastectomy breast cancer radiation therapy. In summary, Exogenous fibronectin diminishes wound progression, by increasing angiogenesis & cell proliferation. This suggests that enhances healing by stimulating the appearance of fibroblasts into the wound site and development of granulation tissue. This acceleration of the repair process may have an important application in the healing of skin chronic wounds.